The Influence of Customer Satisfaction, Brand Image, and Digital Marketing on Interest in Buying Omg Skincare Among Students in Yogyakarta City - Deblina Intan Kartika; Eko Prasojo (BHATARA: Jurnal Multidisiplin Ilmu, 2026)
This study aims to analyze the influence of Customer Satisfaction, Brand Image, and Digital Marketing on Purchase Intention of OMG Skincare among students in Yogyakarta City. The research employed a quantitative approach using an explanatory research method. The population consisted of students in Yogyakarta City who were familiar with or had received information about OMG skincare products. The sampling technique used was purposive sampling, involving 150 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The results indicate that Customer Satisfaction has a positive and significant effect on Purchase Intention, with a t-value of 2.095 and a significance level of 0.038. Brand Image also has a positive and significant effect on Purchase Intention, with a t-value of 2.977 and a significance level of 0.003. Digital Marketing has a positive and significant effect on Purchase Intention, with a t-value of 6.814 and a significance level of 0.000. Simultaneously, Customer Satisfaction, Brand Image, and Digital Marketing significantly influence Purchase Intention, as indicated by an F-value of 94.775 and a significance level of 0.000. Digital Marketing is the most dominant variable, with a beta coefficient of 0.573. The coefficient of determination (R²) is 0.661, indicating that 66.1% of the variation in Purchase Intention can be explained by Customer Satisfaction, Brand Image, and Digital Marketing, while the remaining 33.9% is influenced by other variables not examined in this study.